Charakterisierung von Schüttschichtmaterialien für den Einsatz in Filtern für häusliche Holzfeuerungsanlagen (Studienarbeit) - Schlattmann, Ulrich; Beimdiek, Janis

Innovative Lehre = kreative Lernende? Beforschung eines kunstdidaktischen Lehr-Lernkonzepts - Schmidt, Rebekka; Theis, Julia (Hochschullehre erforschen)

Kunstdidaktik vernetzen. Ein Fortbildungskonzept für Kunstlehrkräfte - Schmidt, Rebekka; Waffner-Labonde, Annika; Welzel, Jana (Kunst- und Musikunterricht im digitalen Wandel. Konzepte und Materialien für die Lehrer*innenaus- und weiterbildung. Themenheft der Zeitschrift DiMawe – Die Materialwerkstatt)

Inklusion braucht Begegnung. Bereits in der Lehrkräftebildung die Grundlagen für gelingende Inklusion anbahnen - Schmidt, Rebekka (Die Bildung Aller – Kunstpädagogik und Inklusion)

Analysis of the Segregation Phenomena of Wood Fiber Reinforced Plastics - Moritzer, Elmar; Flachmann, Felix; Richters, Maximilian; Neugebauer, Marcel (Journal of Composites Science)

Inklusion im Kunstunterricht - Schmidt, Rebekka (Lexikon der Kunstpädagogik)

Online-Videokonferenzen als virtueller Lernraum für Fremdsprachenlernende und Fremdsprachenlehrende - Prikoszovits, Matthias

Reziprozität und das alteritäre Dritte – Über die wechselseitigen Verflechtungen von PageRank und sozialen Medien - Schulz, Christian (Behemoth . A Journal on Civilisation)

INVESTIGATION OF THE PROCESS PARAMETERS AND GEOMETRY DEPENDENT SHRINKAGE BEHAVIOR OF RASTER LINES IN THE FUSED DEPOSITION MODELING PROCESS - Moritzer, Elmar; Hecker, Felix (Proceedings of the 33rd Annual Freeform Fabrication Symposium)

Perspektiven feministischer Digitalisierungsforschung: Querschnittsthemen gesellschaftlicher Transformation im komplexen Zusammenspiel - Richter, Susanne (Feminismen in der Sozialen Arbeit. Debatten, Dis/Kontinuitäten, Interventionen)

Hierarchischen Ordnungen auf der Spur in digitalen Räumen - Richter, Susanne (Freie Assoziation)

YouTube, Männlichkeiten und die Genese von Körpern. Geschlechteranalytische und erziehungswissenschaftliche Einsätze - Hoffarth, Britta; Richter, Susanne; Wehren, Sylvia (Materialität – Digitalisierung – Bildung)

Nachhaltige Softwareentwicklung - Von der Inhouse-Lösung zur Open Source-Community am Beispiel von MerMEId - Henny-Krahmer, Ulrike; Stadler, Peter

Rezension zu: Fickers, Andreas/Griset, Pascal: Communicating Europe. Technologies, Information, Events, Basingstoke, Hampshire 2019 - Schmitt, Martin (Francia-Recensio)

Ausstellungsrezension: Back to Future. Technikvisionen zwischen Fiktion und Realität, 03.12.2021 – 28.08.2022 Berlin - Schmitt, Martin (H-Soz-Kult)

Tagungsbericht: Ethik der Digitalstadt - Herausforderung der Datensouveränität, 03.12.2021 – 03.12.2021 Darmstadt - Schmitt, Martin (H-Soz-Kult)

What is Missing in XAI So Far? - Schmid, Ute; Wrede, Britta (KI - Künstliche Intelligenz)
Abstract With the perspective on applications of AI-technology, especially data intensive deep learning approaches, the need for methods to control and understand such models has been recognized and gave rise to a new research domain labeled explainable artificial intelligence (XAI). In this overview paper we give an interim appraisal of what has been achieved so far and where there are still gaps in the research. We take an interdisciplinary perspective to identify challenges on XAI research and point to open questions with respect to the quality of the explanations regarding faithfulness and consistency of explanations. On the other hand we see a need regarding the interaction between XAI and user to allow for adaptability to specific information needs and explanatory dialog for informed decision making as well as the possibility to correct models and explanations by interaction. This endeavor requires an integrated interdisciplinary perspective and rigorous approaches to empirical evaluation based on psychological, linguistic and even sociological theories.
Keywords: Artificial Intelligence

Explainable AI - Schmid, Ute; Wrede, Britta (KI - Künstliche Intelligenz)
Keywords: Artificial Intelligence

AI: Back to the Roots? - Wrede, Britta (KI - Künstliche Intelligenz)
Keywords: Artificial Intelligence

Which “motionese” parameters change with children's age? Disentangling attention-getting from action-structuring modifications - Rohlfing, Katharina; Vollmer, Anna-Lisa; Fritsch, Jannik; Wrede, Britta (Frontiers in Communication)
Modified action demonstration—dubbed motionese— has been proposed as a way to help children recognize the structure and meaning of actions. However, until now, it has been investigated only in young infants. This brief research report presents findings from a cross-sectional study of parental action demonstrations to three groups of 8–11, 12–23, and 24–30-month-old children that applied seven motionese parameters; a second study investigated the youngest group of participants longitudinally to corroborate the cross-sectional results. Results of both studies suggested that four motionese parameters (Motion Pauses, Pace, Velocity, Acceleration) seem to structure the action by organizing it in motion pauses. Whereas these parameters persist over different ages, three other parameters (Demonstration Length, Roundness, and Range) occur predominantly in the younger group and seem to serve to organize infants' attention on the basis of movement. Results are discussed in terms of facilitative vs. pedagogical learning.
Keywords: Social Sciences (miscellaneous); Communication